Optimalisasi Peran Sedekah dan Bantuan Sosial dalam Meringankan Beban Ekonomi Masyarakat Pada Kegiatan KKN di Desa Campagaya: Optimization of Alms and Social Assistance in Easing Economic Burdens Through KKN in Campagaya Village - Sri Ujiana Putri (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2026)
This community service article describes the optimization of alms (sadaqah) and social assistance programs in easing the basic economic burdens of vulnerable residents and strengthening social empathy during the Kuliah Kerja Nyata (KKN) program in Campagaya Village, Galesong District, Takalar Regency. The program is positioned as community service rather than impact research on long-term economic welfare. Its objectives are to distribute assistance to eligible beneficiaries, provide short-term support for basic household needs, and build community trust and sympathy toward KKN social-religious activities. The method applied was a participatory community service approach using Participatory Action Research (PAR), direct door-to-door delivery, and community-based distribution. Beneficiaries were identified through observation, coordination with village officials, and vulnerability criteria, such as low-income households, elderly residents, widows, and families whose income depends on seasonal work. Program success was assessed through beneficiary accuracy, distribution records, documentation, brief interviews, and community participation. The results indicate that the iftar and basic-food-package programs helped reduce short-term household expenditure, encouraged gratitude and positive responses among beneficiaries, and strengthened cooperation among students, village officials, donors, and residents. Nevertheless, the program remains consumptive and short-term; therefore, future activities should be developed into productive assistance, skills training, or micro-enterprise mentoring so that social assistance can contribute more sustainably to community empowerment.